Voluntary Disclosure Quality and Analyst Coverage - Warren, James D. (The Accounting Review, 2025)
ABSTRACT Prior work documents that managers increase the quantity of earnings guidance provided after exogenously losing coverage from an equity analyst. I examine how analysts influence guidance quality. I find that following an exogenous reduction in analyst coverage, managers issue earnings guidance that is lower quality (i.e., it is less accurate). This result varies predictably based on managers’ incentives, features of the firm’s analyst coverage, and the presence of other intermediaries. Overall, my findings identify a situation in which guidance quantity and quality move in divergent directions and highlight that analysts can be an important determinant of voluntary disclosure quality. JEL Classifications: G10; G17.